Students’ knowledge and process skills in learning grade-8 chemistry - Bete, Aisie Oyammi (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2020)
Determining the knowledge and skills of students are identified as aspects in enhancing the students’ academic performance in sciences. Using the research instrument composed of test items and process skills checklist, data were gathered from 332 grade 8 students from the seven (7) public high schools in the Division of Santiago City, Philippines to assess their knowledge and science process skills in learning grade 8-Chemistry. Standard score (z-score) and descriptive statistics were used to analyzed the data. It was revealed that the student-respondents’ knowledge belongs to “developing proficiency level” while their process skills were rated as poor in their grade 8-Chemistry subject. In using the z-scores, most of the respondents are partially proficient in their scientific knowledge and skills. Based from the result, specific topics in grade 8 chemistry that needs an intervention material were identified. These intervention materials will be subjected to validation and further assessment. In improving the level of process skills and knowledge, students are encouraged to participate in different chemistry activities and for the teachers to elevate their science instruction and students’ academic performances.